Menominee County aid : hearings beforee the Subcommittee on Employment and Manpower of the Committee on Labor and Public Welfare, United States Senate, Eighty-ninth Congress, first and second sessions, on S. 1934, a bill authorizing the Secretary of Health, Education, and Welfare to make certain grants to Menominee County, Wisconsin, and for other purposes. November 10 and 11, 1965, and February 17, 1966 (U.S. Government Printing Office, 1966)
Considers (89) S. 1934, to authorize HEW grants to Menominee County, Wis., to fund programs benefiting the Menominee Indian Tribe, including education, welfare, health (particularly tuberculosis eradication), sanitation facilities, and studies of the county's lumber and recreational resources.